The point-slope form of a line is given by the formula:
\[ y - y_1 = m(x - x_1) \]
Where:
- \( m \) is the slope of the line.
- \( (x_1, y_1) \) is a point on the line.
In your case, the point is \( (3, 1) \) and the slope \( m \) is \( -2 \).
Substituting these values into the formula, we get:
\[ y - 1 = -2(x - 3) \]
So, the equation in point-slope form is:
\[ y - 1 = -2(x - 3) \]
Responses to fill in:
- \( m = -2 \)
- \( (x_1, y_1) = (3, 1) \)
You can now place these responses into the point-slope formula as indicated.